The Impact of Syrian Immigrant Patients on Health Service Delivery: The Case of Istanbul - Ekrem Sevim; Mustafa Nal (Association of Nurse Managers, 2021)
Aim: The study investigates service delivery impacts to Syrian patients on the Turkish health care system. Method: The study was carried out in a retrospective and used the cross-sectional descriptive design using the data of Syrian patients served in public and private health institutions throughout Istanbul in 2018. Results: Healthcare services were provided to 1,419,069 Syrian patients in health institutions in Istanbul in 2018. This number constitutes 1.43% of general patient admissions. While the ratio of Syrian patients to outpatient clinic admissions was 1.05%, the rate for emergency services admissions was 2.82%. In addition, the rate of Syrian patients in general admissions was 1.43%, while the rate among inpatients was 6.10%. Conclusion: Turkey, despite having a health workforce and technical possibilities (numbers of hospital beds, MR and CT devices) to have less opportunities from OECD countries, which also share these resources with Syrian patients. Turkey offers health services to a substantial amount of Syrian patients. Immigrant Syrian patients constitute 1.43% of general admissions to hospitals. It is thought that this small health service burden will not adversely affect the delivery of health services.